Identifying Relevant Internet of Things (IoT) Topics and Authentic Mini Projects to Develop a Micro-credential Curriculum at Malaysian Community Colleges - Techanamurthy, Umawathy; Ahmad, Fadhlina; Kahar, Noorfadhilah; Salahuddin, Ana Rohana Pataniah; Ahmad, Zanariah (Journal of Technical Education and Training, 2024)
The Internet of Things (IoT) is a crucial course in Information Technology programs, merging electronic circuit concepts with programming skills to create interconnected devices. This study aimed to design a Malaysian Community College micro-credential curriculum for IoT by identifying relevant theoretical and practical topics and mini-projects. A need for a micro-credential module with suitable instructional materials was identified, enabling learners to apply theoretical concepts through mini-projects. Using the Fuzzy Delphi (FD) method, data from 19 experts via semi-structured interviews were analyzed to design the Fuzzy Delphi instrument. This instrument was distributed to 30 industry experts and academic practitioners, who ranked the elements on a five-point Likert scale. Fuzzy evaluation to establish consensus for inclusion requires an average expert agreement of 75%, a d-construct threshold of 0.2, and an average fuzzy number of 0.5. Consensus was reached for six out of nine theoretical topics and nine out of 13 practical topics. “Fundamental concepts of IoT” was deemed the most critical theoretical topic with 97% consensus, while "basic connectivity of IoT hardware" was the top practical topic with 100% consensus. For mini-projects, experts accepted two out of nine theoretical topics and nine out of 13 hands-on topics. The top authentic projects were “Air Quality Monitoring” and “Smart Home Security”, with 83% and 80% consensus, respectively. This study lays the groundwork for developing learning outcomes and assessment strategies for a micro-credential course on IoT at Community Colleges to equip TVET students with industry-relevant competencies, thus making them more employable.